Biomarkers of viral and bacterial infection in rhinovirus pneumonia - Hartiala Maria; Lahti Elina; Toivonen Laura; Waris Matti; Ruuskanen Olli; Peltola Ville (FRONTIERS MEDIA SA, 2025)
Background
Rhinovirus (RV) is often detected in children hospitalized with pneumonia, but the role of RV in causing pneumonia is still unclear.
Methods
White blood cell count, C-reactive protein, procalcitonin, and myxovirus resistance protein A (MxA) levels were determined from blood samples in children (n = 24) hospitalized with radiologically verified pneumonia. Respiratory viruses were identified from nasal swabs by using reverse transcription polymerase chain reaction assays. Among RV-positive children, the cycle threshold value, RV subtyping by sequence analysis, and the clearance of RV by weekly nasal swabs were determined. RV-positive children with pneumonia were compared to other virus-positive children with pneumonia, and to children (n = 13) with RV-positive upper respiratory tract infection from a separate earlier study.
Results
RV was detected in 6 children and other viruses in 10 children with pneumonia (viral co-detections excluded). All RV-positive children with pneumonia had high white blood cell counts, plasma C-reactive protein or procalcitonin levels, or alveolar changes in chest radiograph strongly indicating bacterial infection. The median cycle threshold value for RV was low (23.2) indicating a high RV load, and a rapid clearance of RV was observed in all. Blood level of viral biomarker MxA was lower among RV-positive children with pneumonia (median 100 μg/L) than among other virus-positive children with pneumonia (median 495 μg/L, p = 0.034) or children with RV-positive upper respiratory tract infection (median 620 μg/L, p = 0.011).
Conclusions
Our observations suggest a true viral-bacterial coinfection in RV-positive pneumonia. Low MxA levels in RV-associated pneumonia need further studies.